"I'm energized to" & "I'm able to": A dual-path model of the influence of workplace spirituality on high-speed railway drivers' safety performance. (March 2023) - Liu, Yuanyuan; Zhang, Fan; Liu, Pingqing; Liu, Yunshuo; Liu, Shuzhen
Highlights: From the perspective of spiritual driving force, we found the key antecedent of safety performance – workplace spirituality. Workplace spirituality had a positive impact on high-speed railway drivers' safety performance. From the perspective of internal causes, we found and verified the psychodynamic mechanism affecting safety performance. Work passion and self-efficacy mediated the relationship between workplace spirituality and safety performance. Based on the model of proactive motivation and conservation of resources theory, a dual-path model of the influence of workplace spirituality on high-speed railway drivers' safety performance was constructed. Under the influence of workplace spirituality, high-speed railway drivers would be not only more "energized to" but also more "able to" take part in safety work. Abstract: Workplace safety has always been at the core of the sustainable development of high-speed railways in China, where drivers are a significant factor in railway systems in terms of ensuring safe operation. As a spiritual resource perceived by individuals in the workplace, workplace spirituality can improve the safety performance of individuals by internally stimulating their self-efficacy and passion for work. Under the influence of workplace spirituality, drivers are not only likely to be more "energized to" take part in safety work, but also more "able to". Based on the model of proactive motivation and conservation of resources theory, a dual-path model was constructed in the present study to explore the influence of workplace spirituality on the safety performance of high-speed railway drivers as well as the mediating effects of self-efficacy and passion for work. Through the analysis of the data from high-speed drivers in 10 railway bureaus of China (N = 325), workplace spirituality was found to be positively related to safety performance. At the same time, the dual-path model was supported, that is, the mediating effects of self-efficacy and passion or work were successfully confirmed, respectively. The present study provides new insights into the management and cultivation of high-speed railway drivers as well as the safety development of organizations both theoretically and practically.